PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI DI MA SABILUL HASANAH - Yulia Tri Samiha; Syarifah Syarifah; Puput Maryati (Program Studi Pendidikan Biologi, Fakultas Pendidikan Ilmu Eksakta dan Keolahragaan, IKIP Budi Utomo Malang, 2019)
The problem that we need to be solved in the world of our education is the weak learning process. The learning process in the classroom is still directed at the child's ability to memorize information. While biology requires logical and reasonable learning to be accepted and absorbed by the brain so that it can last long. The aim of the research is to know the influence of course review horay learning toward student’s of cognitive learning class ten in the subject matter cell in MA Sabilul Hasanah Kecamatan Sembawa Kabupaten Banyuasin. This research method used quasi-experimental design with a quantitative approach research pretest-posttest control group design. The sample is taken by using purposive sampling techniques. The sample was grade XI MIA 2 as an experimental class and class XI MIA 1 as the control class. The instrument used in this research is a test to measure student’s cognitive learning about the cognitive categories C1-C4. Data analysis use the t-test, data on the calculation difference average posttest both groups earned value t-test much as 4,806 while value t-table with significant level5% with degrees of freedom (dk) 42 is equal to1,684, it can be said that t-test > t-table means the alternative hypothesis (Ha) be accepted and the null hypothesis (H0) rejected. It can be concluded that there is a significant influence of course review horay learning toward student’s of cognitive learning class eleven in the subject matter cell inMA Sabilul Hasanah.